If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2m + 9)(m + -7) = 0 Reorder the terms: (9 + 2m)(m + -7) = 0 Reorder the terms: (9 + 2m)(-7 + m) = 0 Multiply (9 + 2m) * (-7 + m) (9(-7 + m) + 2m * (-7 + m)) = 0 ((-7 * 9 + m * 9) + 2m * (-7 + m)) = 0 ((-63 + 9m) + 2m * (-7 + m)) = 0 (-63 + 9m + (-7 * 2m + m * 2m)) = 0 (-63 + 9m + (-14m + 2m2)) = 0 Combine like terms: 9m + -14m = -5m (-63 + -5m + 2m2) = 0 Solving -63 + -5m + 2m2 = 0 Solving for variable 'm'. Factor a trinomial. (-9 + -2m)(7 + -1m) = 0Subproblem 1
Set the factor '(-9 + -2m)' equal to zero and attempt to solve: Simplifying -9 + -2m = 0 Solving -9 + -2m = 0 Move all terms containing m to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2m = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2m = 0 + 9 -2m = 0 + 9 Combine like terms: 0 + 9 = 9 -2m = 9 Divide each side by '-2'. m = -4.5 Simplifying m = -4.5Subproblem 2
Set the factor '(7 + -1m)' equal to zero and attempt to solve: Simplifying 7 + -1m = 0 Solving 7 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1m = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1m = 0 + -7 -1m = 0 + -7 Combine like terms: 0 + -7 = -7 -1m = -7 Divide each side by '-1'. m = 7 Simplifying m = 7Solution
m = {-4.5, 7}
| =x^2+40x-100 | | -2x-6-3x=1 | | 0.67x-3.5=2.25 | | =2x^2+8x+8 | | x=2+0.5y | | =2x^2 | | 2k+4=10 | | =x^2-100x+2500 | | x=-4-9(-1) | | 3x+7-9x=2(8x-5) | | v^2+5v-9= | | 14x^2+29x-15=0 | | 4x^2-108=5x^2+21x | | -12-27y+12y=3 | | 6.5x-2.58=3.9-4.3x | | 0.25x-0.875=0.625 | | 5xy+1=4y-9x | | -8x=17 | | 6a^2+54a+48=0 | | 3x*5y*2z=5 | | 21x-5=9+14x | | 25c^2-9=0 | | 3x*5y*2z=0 | | ab+ax=c-ax | | 4u^2+9u+5= | | (35x-16)=31x | | 0.67x+0.3=2.4 | | B-4[B-3(5-B)]= | | t(7t+1)= | | 100w^2-9=0 | | 6x+3=3x-21 | | 2x+4=6x-2 |